Terapi Pijat untuk Meningkatkan Kualitas Tidur pada Lansia Binaan Stikes Bala Keselamatan Palu - Ni Luh Emilia; Meilin Anggreyni; Nova Natalia Beba; Juliana Neng Rifka Sarman; Sabarulin S; Yulian Heiwer Matongka (PT.Mantaya Idea Batara, 2022)
One of the health problems experienced by elderly is sleep disturbances both in quality and quantity which can cause effects such as forgetfulness, confusion and disorientation, if it IS happened in long term it will cause trauma. The purpose of this community service is to apply the results of a research is that massage therapy to the elderly in improving sleep quality. The method used was the applying of massage therapy directly given to the elderly assisted by health science college of the salvation army Palu which were consisted of 22 people, it began with an examination of the sleep quality and continued with the applying of 8 times massage therapy which were carried out for 2 months every Friday morning. Result: This massage therapy can improve the sleep quality of the elderly because in the pre test it was found that all the elderly experienced sleep quality disorders and in the post test, it was found that there were 17 of 22 elderly already had good sleep quality but there were still 5 elderly who had mild sleep quality disorders. It is hoped that health workers will continue to apply complementary therapies to the community so that they can improve the health of the community.